Women in calypso : hearing the voices - Maison-Bishop, Carole Nathalie ([s.n.] [S.l.], 1994)
Seeks to explore the lives of women who are singing calypso in the Caribbean, attempting to determine what has motivated them to pursue this occupation and what are some of the obstacles they face as they perform. Focuses on women calpsonians in Barbados, Guyana and Trinidad and Tobago.